Broadband linear‐to‐circular polarization reflector using anisotropic metasurface. Issue 7 (12th April 2021) - Long, Fei; Yu, Shixing; Yang, Zhengyi; Li, Xucheng; Ding, Zhao; Zhang, Zhengping
Abstract: A high‐performance polarization reflector is introduced based on anisotropic metasurface. This structure can convert a linearly polarized (LP) incident electromagnetic (EM) wave into a circularly polarized (CP) reflection wave. The unit cell of the proposed metasurface is made of metallic patch imprinted on the top surface of a metal‐backed single‐layer dielectric substrate. The shape of this metallic patch is a combination of a deformed Jerusalem cross and two deformed L. The simulation results show that the LP incident EM wave is converted to CP reflected wave from 7 to 19.4 GHz, which the bandwidth of axis ratio less than 3 dB is 12.4 GHz and the relative bandwidth is 94%. The current distributions and equivalent circuit model are given to analyze the generation of circularly polarized waves. To verify the metasurface structure performance, a sample consisting of 24 × 24 unit cells is fabricated and measured. The experimental and simulation 3‐dB AR bandwidth are basically consistent with each other, which verify the properties of the design. The proposed metasurface structure has potential application in microwave sensors and antenna design to manipulate the polarization states of EM waves.